Childhood - adolescence - democracy. The contingency, loss and normalization of the phenomenon of adolescence in modern societies - Dietrich Benner; Dariusz Stępkowski (The Francis de Sales Scientific Society (TNFS.PL), 2023)
Contrary to appearances, childhood and adolescence are not only biological phenomena, but also something overtly historical. Thus, they can and must be considered in the context of democracy. The article is divided into four parts. First, the authors recall that in Greek paideia, childhood was hardly given thought and that it was only the Renaissance that saw changes to the concept of man, which led to crystallizing the concept of modern childhood and youth. The second section reconstructs the meaning of the terms "childhood" and "adolescence" in the views of Jean Jacques Rousseau. The theme of the third part is the historicity of childhood, adolescence and adulthood, which the authors discuss against the background of Neil Postman's thesis about the disappearance of childhood and adulthood. In the fourth and final section, the authors attempt, first of all, to clarify what really is disappearing forever, and what remains despite transformations, and, secondly, to indicate the central issues in the relationship between childhood, adolescence, and democracy.